The role of essential requirements of a democratic law-state in the constitutional practice of the Czech Republic - Tomoszek, Maxim (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
When defining the content of essential elements of a democratic Rechtsstaat/ rule of law, it is necessary to take into account in particular the fact that this concept plays five possible roles in the constitutional system of the Czech Republic: the eternity clause, the frame of reference in constitutional review, the material core of the Constitution, the constitutional identity of the Czech Republic, and as a set of core values of the Czech Constitution. Essential elements of a democratic rule of law, in connection with the founding ideas of the Constitution of the Czech Republic, contain both a universal and a specific component. It is hard to imagine a constitutional identity that only duplicates the constitutional identities of other states, on the other hand even in the Czech constitutional identity there is certainly room for the Czech Constitutional Framers to accept the universal principles recognized in the family of Western democracies. This further defines the particular principles understood as essential elements of a democratic rule of law, in the meaning of Art. 9 para. 2 of the Czech Constitution.